Filum Terminale Needle Placement During Caudal Epidural Steroid Injection. Issue 8 (30th March 2017) - Ramsook, Ryan R.; Spinner, David; Doshi, Rajiv R.
Abstract: Objective. Caudal epidural steroid injections (ESIs) are commonly used to treat lumbar radicular pain. Touhy needles are placed under live fluoroscopic guidance to ensure epidural administration of medication. This is a case report of direct needle and catheter placements into and through the filum terminale during a caudal approach to the epidural space. Design. Single case report. Setting. Beth Israel Deaconess Medical Center. Patient. A 69-year-old woman who suffered from chronic low back and leg pain from lumbosacral radiculopathy, failed back surgery syndrome, and lumbar facet arthropathy. Interventions. Caudal epidural steroid injection. Outcome Measures. Patient safety. Results. The needle and catheter placement were confirmed via intrathecal contrast spread to be in the filum terminale, which prompted abortion of the procedure. Conclusions. Although caudal ESI is a relatively safe and routine intervention, care must be taken to ensure proper placement of needle, catheter, and injectate. While contrast is injected to ensure appropriate epidural spread, it serves also to reveal unexpected and unwanted spread. We present the first report of a needle being inserted directly into the filum terminale during a caudal ESI.